ANALISIS PERBEDAAN HARGA SAHAM, ABNORMAL RETURN, DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH STOCK SPLIT SAHAM - Farihah Shufiyani Muin Putri (2022)
This research is in the form of quantitative research that aims to determine differences in stock prices, abnormal returns, and stock trading volumes before and after the stock split. The sample selection in this study was carried out using a purposive sampling method and obtained a sample of 58 companies from companies listed on the Indonesia Stock Exchange and carrying out stock split corporate actions during the 2016 until 2020 period. Hypothesis testing in this study used the SPSS version 28 program using the Paired Sample T-test method for data that is normally distributed and the Wilcoxon Signed-Rank Test for data that is not normally distributed. The result of the research is that there is no difference between stock prices before and after the stock split, while there is a difference between abnormal returns before and after the stock split, and there is a difference between the stock trading volume before and after the stock split.